Experimental determination on the performance and emission characteristics of delonix regia oil methyl ester and its blends on single cylinder diesel engine. (2021) - Dinesh Kumar, V.; Mrityunjayaswamy, K.M.; Chinnapandian, M.; Hemadri, Vinayak B.
Abstract: In general the fossil fuels contribute nearly 80% of the world's energy needs. The fossil oils are fuels that are derived from ancient animals and micro- organisms and its formation in general requires millions of years and thus they are said to be non-renewable energy sources. India depends on other countries for the import of petroleum resources and huge amount is being spent every year. As India is rich in agricultural resources, it is very easy to derive biodiesel from vegetable oil/plant seed. In this paper the performance and emission characteristics of delonix regia oil methyl ester and its blends are investigated experimentally on a single cylinder diesel engine running at a constant speed of 1500 rpm from no load to full load in the incremental of 20%. The seed has an oil content of 27% respectively. It is observed from the result that the blend B25 resulted in better brake thermal efficiency which is closer to that of diesel and better than the other blends. The blend B25 also resulted in relatively less exhaust emission when compared with diesel.